Karakteristik fisikokimia biji kakao (Theobroma cacao L) single-origin Sumbermanjing Wetan, Malang terfermentasi dengan variasi suhu dan lama penyangraian: Physicochemical characteristics of single-origin cocoa beans (Theobroma cacao L.) from Sumbermanjing Wetan, Malang fermented with variations in temperature and roasting time - Elianarni, Dahlia; Lestar, Ayu; Harini, Noor; Manshur, Hanif Alamudin (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
Cocoa is one of the leading commodities in Sumbermanjing Wetan, Malang, East Java, Indonesia. In this study, only one source of cacao was used, so it is called single-origin. The cocoa beans produced by farmers are still of low quality, especially in terms of the strength of the aroma, color, and distinctive chocolate taste. Fermentation of cacao beans can repair the physicochemical and sesory quality. Roasting are important stages in the processing of cocoa beans which significantly contribute to the development quality of flavor and aroma that caused by heat. Several factors can influence roasting are temperature and duration. This research aimed to determine the effect of temperature and duration of roasting on the physicochemical characteristics of fermented cocoa beans. The method used was a factorial Completely Randomized Design (CRD) with treatment variations in temperature A (120 C; 140 C; 160 C) and time B (20 minutes, 40 minutes, 60 minutes). Higher temperatures and longer roasting times can reduce the yield, color intensity, and moisture content of cocoa beans and increase the pH level. The best treatment was obtained at A2B1 with a temperature of 140 °C and a roasting time of 20 minutes which had a yield of 76%; brightness level (L) 37; degree of redness (a) 5.4; yellowness level (b) 1.75; pH level 4.885;  water content 2.9%; fat content 48.12% and polyphenols 6.32 mgAE/g extract.